THE EFFECT OF SUB-CLINICAL INFECTION WITH HAEMONCHUS CONTORTUS ON PRODUCTION PERFORMANCE IN THE ‎PREGNANT EWES - T. Jerjees , M.; A. Ali , D.; M. Al-Saquar ‎, I. (The Iraqi Journal of Veterinary Medicine, 1987)
Fourteen Bulgarian pregnant ewes (three months of gestation), were used and divided in two groups, one group was inoculated with 500 infective larvae /kg. body weight, the other group remained non-infected control. Productive parameters, blood changes were recorded and faecal egg counts were examined weekly. Marked reduction in food intake was recorded in infected ewes, especially during prelambing period. No obvious differences were noted between both groups after lambing. Slight differences in body weight gain were recorded between both groups until labour, while after lambing, the weight losses of infected ewes were highly significant 1%. No effect of infection has been seen on fleece weight, while significant depression in the haemoglobin and packed cell volum of infected group during the pre-parturient period, and the high reduction occured at week (7). Generally the results indicated that there were variations in resistance of ewes or its susceptibility to parasitic infection.